Absenteeism and the role of Love Life programmes in the reduction of absenteeism at the two secondary schools at Marapong - Bokgola, Mogalapitja Sybil (My University, 2007)
This report describes the research conducted at two secondary schools at Marapong. The title of this report is ABSETEEISM AND THE CONTRIBUTION OF LOVE LIFE PROGRAMMES IN THE REDUCTION OF ABSENTEEISM. The research is taking part in the third and fourth pillars of the research programmes in Adult Education namely: young adults at risk and health adult education. The aims of this study are two fold. Firstly, to identify and describe problems that might have contributed in making youth to stay away from school and secondly, to evaluate the impact of Love Life programmes on the reduction of absenteeism in participating secondary schools at Marapong. The following research questions were formulated, for me to be aware of the above-mentioned aims.  What is the rate of absenteeism?  What are the reasons of absenteeism at these two secondary schools?  What are the characteristics of Love Life programmes?  What is the impact of Love Life programmes in the reduction of absenteeism?  How can the programmes be improved? To provide the most valid, accurate answers possible to the above- mentioned questions, a descriptive research with both qualitative and quantitative approaches were used. Different instruments were used to collect data. The participants are the principals, co-ordinators of the Love Life programmes, educators, the School Governing Body (SGB), Representative Council of Learners (RCL), participants and non-participants of the two secondary schools. The most important findings have to do with different factors, which are related. The findings are presented into three factors: socio-economic, school and personal. Many problems relating to the socio- economic aspects were; poverty, overcrowding in families, lack of parental involvement, peer pressure, teenage pregnancy and the child support grants. At the school level, most problems the youth were facing were; inadequate supervision, presentation of lessons and labelling. On the basis of the data provided, several improvements need to be made. In the last chapter of this report, recommendations are given on problems experienced by youth and the school. These problems concern absenteeism and the role of Love Life programmes in the reduction of absenteeism.
Thesis (M.Ed. (Adult Education)) -- University of Limpopo, 2007
Keywords: Absenteeism; Love life Programmes; Secondary schools; Reduction of absenteeism; Classroom management; Absenteeism (Labor)